Successful Balloon Mitral Valvuloplasty in 21-week Pregnant Patient with Severe Mitral Stenosis: A Case Report and Literature Review - Cynthia Yosephine Silitonga; Nahar Taufiq; Budi Yuli Setianto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Mitral stenosis is the most common manifestation of rheumatic heart disease. Hemodynamic changes during pregnancy increase the burden of the heart in pregnant women with cardiac abnormalities. A 33 years old woman, G3P1A1 is 21 weeks pregnant came to our hospital with a shortness of breath during daily activity, which was worsened since 3 months of pregnancy. The patient has been diagnosed with severe mitral stenosis. The results of echocardiography examination was left atrial dilatation, normal global function and left ventricular with ejection fraction 51%, severe mitral stenosis Wilkin Score 8 with Mitral Valve area 0.53 cm2 and Mitral Valve Gradient 33 mmHg. Subsequently, Balloon Mitral Valvuloplasty was successfully performed. During and after the procedure there was no complication. The fetus was considered in stable condition.